A discrete serotonergic circuit involved in the generation of tinnitus behavior - Meng-Ting Yu; Zhen-Yu Dai; Si-Xin Wang; Ke-Jian Wang; Chun-Hui Qin; Yi-Mei Zhou; Xiao-Tao Guo; Chun-Chen Pan; Jia-Qiang Sun; Jing-Wu Sun; Wei-Heng Chen; Yan Jin; et al. (Proceedings of the National Academy of Sciences, 2026)
Although dysregulated serotonergic neurotransmission has been implicated in the pathophysiology of tinnitus, the precise neural circuit mechanisms underlying this complex sensory neurological disorder remain elusive. In the current study, we investigated whether a serotonergic input from the dorsal raphe nucleus (DRN) to the dorsal cochlear nucleus (DCN), a key auditory brain region whose hyperactivity is associated with tinnitus, modulates behaviors in mice consistent with the presence of tinnitus. Using neural tracing and viral-genetic methods, we identified an anatomically and functionally defined serotonergic subpopulation in the DRN that projects to the DCN (5-HT DRN→DCN neurons). Optogenetic activation of 5-HT DRN→DCN circuit increased spike activity in DCN fusiform cells, exhibiting characteristics consistent with tinnitus-like electrical hyperactivity. Chemogenetic activation of 5-HT DRN→DCN circuit induced tinnitus-related behaviors in mice, which was largely reversed by blocking 5-HT 2A receptors. Additionally, we found that noise exposure increased 5-HT levels in the DCN and the activity of 5-HT DRN→DCN neurons in mice with noise-induced tinnitus-related behaviors. Importantly, chemogenetic inhibition of 5-HT DRN→DCN circuit ameliorated significantly noise-induced tinnitus–related behavior in mice. These results reveal that activation of 5-HT DRN→DCN circuit induces hyperactivity in the DCN sufficient for the perceptual generation and modulation of tinnitus. These findings provide direct evidence that 5-HT neurons in the DRN play an important role in tinnitus and facilitate our understanding of the circuit mechanisms of pathophysiology in sensory neurological disorders.